Cultural malpractice during pregnancy, childbirth, and the postnatal period and its associated factors among women who gave birth once in Dire Dawa city administration, Eastern Ethiopia, in 2021 - Hailu, Mickiale; Mohammed, Aminu; Sintayehu, Yitagesu; Tadesse, Daniel; Abera, Legesse; Abdurashid, Neil; Solomon, Milkiyas; Ali, Momina; Mellese, Dawit; Weldeamaniel, Tadesse; Mengesha, Teshale; Hailemariyam, Tekelebirhan; et al. (Frontiers in Global Women's Health, 2023)
Background: Cultural malpractices are defined as a socially shared views and traditionally accepted behaviors experienced in a certain society that harm maternal health. Worldwide, the period of pregnancy, labor and delivery is embedded with different beliefs, customs, and rituals in different societies that contribute a lot to maternal death. They are responsible for the annual deaths of 303,000 mothers and 2.7 million newborns globally. In developing countries, it accounts for about 5–15% of maternal deaths. In Ethiopia, about 18% of infant deaths occur due to cultural malpractice, and 52% of pregnant mothers give birth at home following cultural customs in Dire Dawa city. The objective of this study was to assess cultural malpractices during pregnancy, childbirth, and the postnatal period among women's who gave birth once in Dire Dawa City, 2021.A community-based mixed study was conducted. A total of 624 study participants were selected through a systematic random sampling technique, and a purposive sampling method was used for qualitative data. The study was conducted in randomly selected Kebele of Dire Dawa City, Eastern Ethiopia, from November 1-December 30, 2021.Data was entered into Epi Data version 4.1 and exported to SPSS version 24 for analysis. Bivariate and multivariate analysis was done, and the degree of association was measured by using the odds ratio with 95% CI and significance was declared at a p-value of < 0.05. The qualitative data was analyzed thematically using ATLAS-ti .The overall prevalence of cultural malpractice during the pregnancy, child birth and postnatal period was 74.6% [95% CI: 70.59%, 77.49%]. Women over the age of 35 were two times more likely [AOR 2.61, 95% CI, 1.45-4.72] to commit cultural malpractice than women aged 15–24 and 25–34. No ANC follow-up were three times more likely to commit cultural malpractice [AOR 3.57, 95% CI, 1.72-7.40], absence of health education was nearly two times more likely to commit cultural malpractice [AOR 1.83, 95%CI, 1.25–2.67], and women whose culture allows harmful traditional practices were nearly two times more likely to commit cultural malpractice than their counterparts [AOR 1.69, 95%CI, 1.29–2.54].In this study, nearly three-fourths of participants were involved in cultural malpractices.